2-MACHINE ORDERED FLOWSHOP SCHEDULING UNDER RANDOM BREAKDOWNS - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1994)
The problem of scheduling on a two-machine ordered flowshop, where machines suffer random breakdowns, is addressed with respect to the individual objectives of makespan and mean flowtime. An optimal sequence with makespan objective is obtained when only one of the two machines suffers random breakdowns. An optimal sequence with respect to mean flowtime is obtained when both machines are subject to random breakdowns.
Keywords: STOCHASTIC SCHEDULING; FLOWSHOPS; MACHINE BREAKDOWNS; MEAN FLOWTIME